Effect of natural aging prior to heat treatment on tensile property of Al-1.2Si-0.5Mg-0.25Fe sheet alloy - Wong, Mee Chu Karen; Daud, Abdul Razak (Penerbit Universiti Sains Malaysia, 2004)
Good formability, good corrosion resistance and reasonably good strength of the 6XXX series aluminum alloys have made them a good candidate for automotive body applications. In Europe, the high formability of Al alloy, AA6016 has made it the main automotive skin alloy, while in North America, AA6111 is a preferred alloy because of its good final strength and good dent resistance (Burger et al., 1995).